AL-FARABI ON HUMANS - Tien Rohmatin (ILMU USHULUDDIN, 2022)
The Discourse about humans to this day continues to be actual and contextual and has always been an important issue. The question of who, what, and where humans are is still a matter of debate among scientists, philosophers, and theologians. In general, among philosophers, scientists, and theologians, humans are understood in three ways: First, the group that holds that humans are only material that occupies space, can be seen, touched, measured, counted, and so on. The second group is having a view that human nature is only the spirit. While the third group has a view that humans are made up of matter and spirit perfectly and simultaneously or consist of body and spirit (soul). This paper describes the thoughts of a Muslim philosopher, al-Farabī about humans. Al-Farabī is a Muslim philosopher who is known as al-Muʿallim al-Thānī (Second Teacher) after Aristotle who was nicknamed al-Muʿallim al-Awwal (First Teacher). An honorary title was given to him for his ability to review the thoughts of Greek philosophers, especially Aristotle. Humans according to Al-Farabī are two-dimensional beings. The physical dimension is in the form of a material body and the spiritual dimension consists of the soul (al-nafs) and spirit (al-rūḥ).